PEDAGOGICAL CONDITIONS OF CREATIVE FORMATION PERSONALITIES OF THE FUTURE TEACHER (Pedagogy of Higher and Secondary Education, 2022)
The article describes objective and subjective conditions of student’s creative personality development in teaching and educational process of higher pedagogical education.
Keywords: creative personality; pedagogical creative work; pedagogical conditions